Distribution of Serotypes, Antimicrobial Resistance and Virulence Genes among Streptococcus agalactiae Isolated from Bovine in China - Zhang, Zhe; Yang, Feng; Li, Xin-pu; Luo, Jin-yin; Liu, Long-hai; Wang, Dan; Zhang, Ya-ru; Li, Hong-sheng (Acta Scientiae Veterinariae, 2019)
Background: Bovine mastitis, a global disease that is responsible for large economic losses each year due to lower milk yield and reduced milk quality. In some countries, especially in China, Streptococcus agalactiae has become one of the most frequently detected pathogen. Antibiotic treatment and vaccine immunization are important strategies for the control of infectious diseases. The main objective of the present study was to evaluate distribution of bovine mastitis pathogens and antimicrobial resistance of S. agalactiae, and contribute to the treatment of bovine mastitis. Materials, Methods & Results:Clinical mastitis samples (n= 1,122) were collected from 27 dairy farms located in 15 different provinces of China during 2012-2018. Thepathogens were identified by 16S rDNA method. Antimicrobial susceptibility was assessed by disc diffusion method. Molecular characteristics was distinguished based on PCR. The results showed that the main pathogens were Streptococcus agalactiae (n= 324, 26.2%), Escherichia coli (n= 287, 23.2%), and Staphylococcus aureus (n= 131, 10.6%). The serotypes of Streptococcus agalactiae were serotype II (53.6%), Ia (44 %) and VII (1.2%), respectively. Streptococcus agalactiae were resistant to kanamycin (93.8%), gentamicin (49.4%), vancomycin (49.4%), tetracycline (35.8%), clindamycin (34.6%) and erythromycin (32.1%). The main resistance genes were ermA (53.1%) and ermB (85.2%). Resistance to erythromycin was attributed to the genes ermA (P < 0.05) and resistance to tetracycline was attributed to the genes tetK, tetM, tetO (P < 0.01). The virulence genes scpB (81.4%), cyl (100%), glnA (76.6%), cfb (98.8%), hylB (98.8%), scaA (69.1%) were detected in almost all isolates. Discussion: In the present study, Streptococcus agalactiae, Escherichia coli and Staphylococcus aureus were the pathogens isolated most frequently from clinical mastitis. In the case of S. agalactiae, we performed capsular serotyping of isolates. As a result, serotype II (53.6%), Ia (44 %) and VII (1.2%) were detected whichrevealed variation in the distinct geographical areas. We found that serotypes (Ia and II) and β-hemolytic have significant correlation (P < 0.01) in all isolated strains. We made an assumption that either in processes of capsular and haemolytic appearance effected the expression of another. The unclear mechanism remains to be resolved in the future. Penicillin was recommended as a preferred antibiotic for the treatment of both human and bovine S. agalactiae infection. In the present study, resistance to erythromycin and clindamycin were observed in 32% and 34.6% of our strains, respectively. The results indicated that the ermB gene was most frequent among the erythromycin-resistant S. agalactiae. However, we found that the susceptibility to erythromycin and gene ermA have a significant interaction, while susceptibility to erythromycin and gene ermB have a not significant interaction by analyzing the relationship of phenotypic and genotypic resistance. The severity of S. agalactiae infections may be determined by various virulence factors. Surface enzyme ScpB, a C5a peptidase, encode by scpB gene, could promote bacterial invasion of epithelial cells by attenuating recruitment of polymorphonuclear leukocytes to the site of infection. In the present study, the scpB gene was found in 81.4% of all strains. The results suggested the cyl, cfb, hylB and scpB genes may play an important role in the virulence of Streptococcus agalactiae pathogens.